GAMBARAN FAKTOR – FAKTOR PENYEBAB TERJADINYA AMENOREA PADA REMAJA PUTRI DI DESA HELVETIA TIMUR KECAMATAN HELVETIA MEDAN PERIODE APRIL-JUNI TAHUN 2012 - Christina Magdalena T. Bolon (Program Studi S1/DIII-Keperawatan Universitas Imelda Medan, 2019)
Amenorrhea is the absence of menstruation for at least 3 consecutive months. Amenorrhoea can be divided into primary amenorrhoea and amenorrhoea sekunder.Amenorea an issue important enough for us to know, especially in adolescents, the World Health Organization (WHO) estimates that the incidence of amenorrhea in teenagers is 10-15%. Where In developed countries such as the Netherlands, the percentage of amenorrhea is quite large at 13%. The incidence of amenorrhea in in Indonesia is quite high. The purpose of this study is to describe the factors that cause the occurrence of amenorrhea in young women. The study was conducted at Jl. East Helvetia district. Helvetia Medan. The population is young women who do not understand about amenorrhoea. The sample size is 40 people. Samples are young women who do not understand about amenorrhoea. Criteria sample respondents are willing to become young women who do not understand about amenorrhoea, in Jl.Istiqomah East Village district of Medan Helvetia Helvetia. From the results of research conducted by the researchers found that the description of the factors that cause the occurrence of amenorrhoea In teenage daughter based knowledge, just as much as 50%, the characteristics of respondents by age most are aged 10-13 years 23.3%, most respondents Information sources are Officers health as much as 20%. Data analysis technique consists of editing, coding, sorting, data entry, cleaning, Expenditure Information. To the community, family and health care professionals should pay attention and a good understanding of and support for young women who do not understand about amenorrhoea, as well as providing good health care accordance 2010-2014 realizing the vision of health development of healthy communities independent and fair.